Remote buprenorphine-naloxone initiation as an essential service for people with chronic pain and opioid dependence during the COVID-19 pandemic: Case reports, clinical pathways, and implications for the future - Hance Clarke; Aliza Weinrib; Yuvaraj Kotteeswaran; Joel Katz; Alvis Yu; Robert Tanguay (Taylor & Francis Group, 2020)
Many health care professions have reacted swiftly to the COVID-19 pandemic. In-person care has been ramped down and telemedicine/telehealth has been thrust to the forefront of clinical care. For people living with chronic pain and often concomitantly dealing with opioid-related issues, this is a time of great stress. With population-wide movements to shelter in place, people living with pain are more isolated, more stressed, and more vulnerable to mental health concerns like depression and anxiety that can increase pain-related suffering. This article presents two case reports of patients struggling with chronic pain and opioid dependence in which a telemedicine-based buprenorphine-naloxone conversion was chosen as a treatment option by two Canadian programs: The Transitional Pain Service at the Toronto General Hospital in Toronto, Ontario, and The Opioid Deprescribing Program in Calgary, Alberta. Both cases presented highlight the use of telemedicine during the COVID-19 pandemic and suggest that there will be substantial need for these services well beyond the apex of the crisis. A buprenorphine-naloxone home induction protocol is presented and we provide insight into important lessons learned regarding the appropriate selection of patients with chronic pain struggling with opioid use disorder for buprenorphine-naloxone conversion. The provision of health care during the COVID-19 pandemic has rapidly forced practitioners to evolve novel health care practices, and these changes will have long-term implications.